Facilitators and barriers to social care in adult primary care: A systematic review using the social-ecological model - Laura Porterfield; Christen M. Walcher; Forrest Jones; Mary E. Jones; Cathy Z. Xie; Quratulanne H. Jan; Zuleica M. Santiago Delgado; Elizabeth M. Vaughan (SSM - Health Systems)
Background: Social care, the assessing and addressing of patients’ health-related social needs, may expand primary care’s impact. However, more information is needed about what primary care teams require to succeed in social care. The aim of this systematic review was to understand facilitators and barriers to social care in adult primary care settings through the lens of the social-ecological model. Methods: Six online databases were searched for studies in adult primary care contexts that addressed facilitators and barriers to social care and were published 2014 to present. Two authors assessed independently for inclusion using a priori criteria. Data was extracted independently by two authors. Study results were assigned and organized by social-ecological model level (individual, interpersonal, organizational, community, policy). Results: 3895 articles were screened and 86 studies included. Organizational factors were the most common level for facilitators (77 %) and barriers (79.1 %). Lack of clinician time, excess workload, lack of community resources, and fee-for-service payment were prominent barriers. Facilitators included social care team members, workflow optimization, EHR integration, resource databases, team training, and community resources. Conclusions: Barriers to social care in primary care are numerous but surmountable through investments in teams, training, infrastructure, and resources. Investing in social services, healthcare structures, and payment systems that support social care work could empower primary care to partner with patients for better health. Registration: The review protocol is registered with the International Prospective Register of Systematic Reviews: Protocol Registration: CRD42024553413